The relationship between phenotypical findings and different karyotypes in children with turner syndrome (Annals of Medical Research, 2021)
Aim: Turner syndrome (TS) is the most common chromosomal disorder in girls. Several systems can be adversely affected in association with genetic disorders. The purpose of this study was to examine the karyotype distribution in patients with TS, frequently seen clinical characteristics, and their relations with the karyotypes.Materials and Methods: Fifty-four cases ranging in age between two and 40 years and diagnosed with TS at three different centers in Turkey between May 2013 and June 2019 were evaluated retrospectively. Results: The patients’ mean age was 17.5±9.3 years. The most common chromosomal anomaly was 45,X (35.2%), followed by low-level mosaic (20.4%), isochromosome (18.5%), deletion (9.3%) and other chromosomal disorders (16.7%). The most common presentation symptom was short stature (66.6%), followed by infertility (12.9%). Cardiovascular pathology was determined in 33.3% of cases, hypothyroidism in 25.9%, ophthalmological problems in 24.1%, renal anomaly in 18.5%, hearing loss in 12.9%, and scoliosis in 9.3% and mental retardation in 16.6%. Obesity was present in 33.3% of cases.Conclusion: Turner Syndrome is a chromosomal disorder affecting several systems. Clinical manifestations in patients with TS can be affected to varying degrees depending on the karyotype.
Keywords: Children; karyotype; phenotype; turner syndrome